2018
DOI: 10.1038/s41374-018-0084-x
|View full text |Cite
|
Sign up to set email alerts
|

Sex dimorphism in ANGII-mediated crosstalk between ACE2 and ACE in diabetic nephropathy

Abstract: Angiotensin-converting enzyme (ACE) and ACE2 play a critical role in the renin-angiotensin system (RAS) by altering angiotensin II (ANGII) levels, thus governing its deleterious effects. Both enzymes are altered by sex and diabetes, and play an important role in the development of diabetic nephropathy (DN). Importantly, previous evidence in diabetic and ACE2-deficient (ACE2KO) males suggest a sex-dependent crosstalk between renal ACE and ACE2. In the present work, we aimed to study the sex-specific susceptibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 69 publications
2
34
0
Order By: Relevance
“…Results of animal studies demonstrated that tissue-specific regulation of ACE2 by sex hormones could contribute to sex-related differences in obesity-hypertension [18]. The modulation and angiotensin II level by ACE2 and ACE could partly explain the sex-specific susceptibility to diabetes and diabetic nephropathy [19]. Further in-depth mechanical studies are warranted to understand the sex-related dimorphism of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Results of animal studies demonstrated that tissue-specific regulation of ACE2 by sex hormones could contribute to sex-related differences in obesity-hypertension [18]. The modulation and angiotensin II level by ACE2 and ACE could partly explain the sex-specific susceptibility to diabetes and diabetic nephropathy [19]. Further in-depth mechanical studies are warranted to understand the sex-related dimorphism of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that ACE2 has three main functions. [5][6][7] First, ACE2 is a powerful negative regulator of RAS, balancing the multiple ACE functions. By targeting angiotensin II, ACE2 shows protective effects in the cardiovascular system and many other organs.…”
mentioning
confidence: 99%
“…In agreement with these results, it was shown that ACE2 expression is decreased in the tubules in human diabetic nephropathy [ 94 ]. The imbalance of the RAAS system in favor of AngII in the context of diabetes results in a more severe kidney damage in males than in females, which is even increased if ACE2 is downregulated [ 95 , 96 ].…”
Section: Pathophysiological Contributions Of Covid-19 Risk Factorsmentioning
confidence: 99%